Unmasking the Porter hypothesis: Environmental innovations and firm-profitability - Sascha Rexhäuser; Christian Rammer (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2011)
We examine impacts of different types of environmental innovations on firm profits. Following Porter's (1991) hypothesis that environmental regulation can improve firms' competitiveness we distinguish regulation induced and voluntary environmental innovations. We find that innovations which reduce environmental externalities reduce firms' profits, as long as they are induced by regulations. However, innovation that increases a firm's material or energy efficiency in terms of material or energy consumption has a positive impact on profitability. This positive result holds both for regulation induced and voluntary innovations, although the effect is significantly larger for regulation-driven innovation.We conclude that the Porter hypothesis does not hold in general for its 'strong' version but has to be qualified by the type of environmental innovation. Our finding rest on firm level data from the German part of the Community Innovation Survey in 2009.
Keywords: Q55; Q58; 330; Environmental innovation; environmental regulation; Porter hypothesis; competitiveness; Umweltpolitik; Umwelttechnik; Innovation; Rentabilität; Internationaler Wettbewerb; Schätzung; Deutschland